Impact of an educational intervention on rational laboratory test ordering and healthcare costs in family medicine - Muhammet Şahinol; Hüseyin Nejat Küçükdağ (Medicine, 2026)
This study aims to analyze the impact of “Rational Laboratory Test Ordering” training given to family medicine residents on their test request habits, number of tests, and costs. A total of 27,085 applications made to the Family Medicine Polyclinic of Düzce University Faculty of Medicine between June 1, 2022, and June 1, 2024, were retrospectively examined. Based on the educational intervention provided to resident doctors on June 1, 2023, the periods before and after were compared in terms of the total number of tests, tests per application/per patient, and costs based on Health Implementation Communiqué prices. After the training, although there was no significant difference in the monthly number of admissions ( P = .660), the average monthly total number of tests decreased from 8382 to 5808 ( P < .001). The number of tests per visit decreased significantly from 7.74 to 5.03, and the cost per patient decreased significantly from 167.37 Turkish Liras (TRY) (4.74 United States Dollars [USD]/ 4.56 Euros [EUR]) to 136.94 TRY (3.88 USD/ 3.73 EUR) ( P < .001). During the 1-year period, a savings of 17.3% (255,009.13 TRY; 7228.15 USD/ 6942.80 EUR) was achieved in the total laboratory costs. Especially, a significant decrease was observed in the requests for sodium, aspartate aminotransferase, and serum free thyroxine, while the requests for alanine aminotransferase and thyroid-stimulating hormone remained stable. The educational intervention significantly reduced unnecessary test requests and costs without narrowing clinical capacity. Changes in specific tests (such as the preference for alanine aminotransferase over aspartate aminotransferase, thyroid-stimulating hormone over serum free thyroxine) suggest that physicians’ test ordering patterns may reflect greater adherence to evidence-based medicine guidelines. The rational laboratory approach serves both economic sustainability and the protection of patients from excessive medicalization within the framework of the principles of quaternary prevention.